Uma política para pobres? Um estudo sobre a atenção primária à saúde no Brasil (1995-2010) - Moisés, Iris da Silva Cabral (2016)
This study of the question whether the Primary Health Care (PHC) can be considered a policy for poor and has as main objective to analyze the challenges of APS from the authors approach defending and criticizing the implementation of this policy. For this, a document search based on some of the main materials released by the Ministry of Health (MOH) was performed, thus representing the official and legal position of the federal government. There was also a literature review in the critical literature on public health and the conduct of primary health care in the country. The study period was from 1995 to 2010 involving two major governments. In this study, we discuss briefly about the development of the health care system in Brazil until the creation of the Unified Health System (SUS) in 1988. Then it is on primary care in the country highlighting the adoption of the Family Health Strategy (ESF) and the creation of Support Centers for Family Health Strategy (NASF). Finally, point to the major differences between the institutional discourse and interpretations that challenge the official version of the APS. From this study it was observed that since the 1990s the neoliberal government policy negatively impacted the health sector, expanded the private area in the provision of services, leaving the Government to basic care for those who cannot afford. Among the challenges identified are the strengthening of PHC and the effective reversal of the direction given to it a range of policy limited to use simple technology, focused on the poor.